A real-time health notification system aimed at enhancing the interaction between animal care staff and researchers promotes animal welfare - Yatkin Emrah; Kulmala Nina; Saukkonen Aija; Maaranen Jukka; Jaakkola Ulla-Marjut (SAGE PUBLICATIONS INC, 2022)
Regardless of the microbiological status of an animal facility, research animals may experience health problems, leading to pain, suffering and distress. Simple and efficient tools are needed to collect data systematically, allowing researchers to react and resolve animals' health issues. We have developed a real-time notification method for recording clinical observations, which caretakers can input into the ELLI record-keeping system, accompanied by a picture or video. A browser-based interface system sends alerts using a three-tier scale (+, 120 hours; ++, 72 hours; +++, 24 hours) by email and/or SMS. The percentage of animal health notifications for rodents was 1.31% in 2016, 1.33% in 2017 and 1.58% in 2018, with 34-44% for coat and skin conditions (wounds, bites and scratches). All other notifications, including environment and behaviour, procedure-specific indicators (weight loss, bleeding and abnormal secretions) and other abnormalities such as eye and teeth malformations, ranged from 5% to 10% during the three-year period. Researchers displayed good compliance by reacting to the notifications within the expected time frame. Most health notifications concerned genetically modified (GM) animals without a predetermined harmful phenotype, regardless of being on project licence or maintenance licence. Health notification records may be useful retrospectively not only to review the health and welfare issues of new GM lines but also to evaluate the actual severity of procedures. The health notification system described here provides valuable information to the veterinarian and the animal welfare body by helping to address specific health conditions and to improve animal welfare and implement the 3Rs.